ANALISIS PENGARUH CASH CONVERTION CYCLE, LEVERAGE, NET WORKING CAPITAL, DAN GROWTH OPPORTUNITY TERHADAP CASH HOLDINGS PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA PERIODE 2010-2015) - Andika, Mhd Septa; Efni, Yulia; Rokhmawati, Andewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The presence of cash in the balance sheet of a company becomes an essential component. Without cash company's activities can not be run. This research aims to analyze and provide empirical evidence related to the effect of cash convertion cycle (CCC), leverage (LEV), net working capital (NWC), and growth opportunity (GO) to cash holding (CH) consumer goods industry companies listed on the Indonesia Stock Exchange in 2010 – 2015. This research uses secondary data collected from financial statement of consumer goods companies from 2010 – 2015. Samples were taken by using purposive sampling technique. Of the 37 consumer goods industry company, they were acquired 17 companies sampled in this study. Data were analyzed using multiple regression analysis. Based on the results of hypothesis testing, the F test, indicating that the variables of CCC, LEV, NWC, and GO simultaneous have an effect on CH. Further more, the t test showed that the CCC, LEV, and GO have significant positive effect on CH. While the NWC variable does not have a significant effect on CH.Keywords : cash holdings, cash